Optimization of Bhabinkamtibmas Performance Through the Sambang Door to Door System to Prevent Criminal Acts of Fraud in the Jurisdiction of the Blitar City Police - Abdurrahman, Muhammad Rendy (Advances in Police Science Research Journal, 2024)
This research was motivated by the significant increase in fraud cases in Blitar City, East Java, which occurred in the last 5 years. This research aims to explore the role of Bhabinkamtibmas in preventing criminal acts of fraud in the region. This research uses a qualitative approach with field research methods (Field Research). Data collection techniques through interviews, observation and document analysis. The research results show that the performance of Bhabinkamtibmas in preventing fraud at the Blitar City Police is still less than optimal due to a lack of knowledge, abilities and personality attitudes. Improvements are needed through collaboration with the Criminal Investigation Unit, implementation of Dikjur, and counseling guidance. Bhabinkamtibmas faces obstacles such as lack of implementation of procedures, multiple tasks, and lack of infrastructure. Corrective steps are needed to improve the performance of Bhabinkamtibmas in preventing fraud.